Impact of health policy based on the self-management program on Cesarean section rate at a tertiary hospital in Taiwan - Ching-Ming Liu; Yu-Jr Lin; Yu-Yun Su; Shuenn-Dyh Chang; Po-Jen Cheng (Journal of the Formosan Medical Association, 2013)
In 2005, a self-management program, based on the global budget system that met the criteria for reducing Cesarean delivery rates, was introduced to obstetric practices in Taiwan. The purpose of this study was to examine the impact of different national health policies on the Cesarean delivery rate at a tertiary hospital. Methods: We constructed a Poisson regression model and conducted an interrupted time series analysis to detect the effects of the implementation of each health policy on Cesarean deliveries. We used data collected at two points before the implementation of the global budget system (GBS) policy (in 2001 and 2002), and at two points after the implementation of the hospital-based self-management (HBSM) policy (in 2005 and 2010). All monthly data were collected at these time points. Results: Between June 2001 and August 2010, the rate of improvement of vaginal birth after Cesarean section (VBAC) during Period 1 revealed that VBAC may have long-term effects (p < 0.001). While there may have been a remarkable immediate improvement in the VBAC rate (p = 0.0276) in Period 3, the long-term effect of VBAC seemed to have decreased during the same period (p = 0.0003). Following the synergistic impacts of health policy implementation during Period 3, the immediate improved total Cesarean section (C/S) rate seemed to be maintained at an average value (p = 0.0183). Conclusion: Over the long term, the C/S rate seemed to reach a plateau; the immediate effect on the VBAC rate was a significant increase consistent with that of the initial health policy implementation.